Prognostic Factors for Patients With Undifferentiated High Grade Pleomorphic Sarcoma of the Spine. Issue 9 (1st May 2019) - Lou, Yan; Wan, Wei; Wu, Zhipeng; Yang, Jian; Xu, Kehan; Huang, Quan; Liu, Tielong; Wei, Haifeng; Yang, Xinghai; Xiao, Jianru
Abstract : Study Design: Retrospective survival analysis of 44 undifferentiated high grade pleomorphic sarcoma (UPS) of the spine. Objective: To identify factors related to overall survival (OS) and help decision making in the treatment of undifferentiated high grade pleomorphic sarcoma of the spine. Summary of Background Data: UPS is an aggressive malignant tumor rarely originating from the spine. Due to its scarcity, only a few studies had been reported to describe the clinical features, treatments, and outcomes of sporadic cases, devoid of evaluation on prognostic factors. Methods: Enrolled in this survival analysis were 44 patients who underwent surgery and adjuvant therapies from January 1999 to December 2015. Kaplan–Meier methods were applied to estimate the overall survival. A multivariate Cox algorithm was applied to recognize factors independently associated with overall survival. Results: Multivariate analysis suggested that age greater than or equal to 55 years (hazard ratio [HR], 3.923, P < 0.001), Eastern Cooperative Oncology Group (ECOG) score four (HR, 4.656, P < 0.001), and subtotal resection or piecemeal total resection (HR, 4.375, P < 0.001) were independently associated with poor overall survival. Conclusion: We identified independent prognostic factors of UPS of the spine. Subtotal resection or piecemeal total resection, age more than or equal to 55 years and ECOG score four are factors adversely affecting overall survival of patients with UPS of the spine. Level of Evidence: 4 Abstract : UPS is an aggressive malignant tumor rarely originating from the spine. Enrolled in this survival analysis were 44 patients which represents the largest series of UPS in the spine. We identified that age ≥ 55 years, ECOG score four and non en bloc resection were independently associated with poor OS.